A rare case of acute colonic pseudo-obstruction leading to colonic perforation in a ventilated patient with cerebrovascular accident - Bandaru, Srinivasa Swamy; Hamed, Heba Abdelhafiz; Al Masalmeh, Fadi Hassan (International Surgery Journal, 2024)
Acute pseudo-colonic obstruction in a patient with a functioning ileocecal valve can be risky, resulting in closed-loop obstruction, significant distention of the colon, and increased chances of colon perforation and ischemia if diagnosis and timely non-operative treatments are delayed. We report a case of acute pseudo-colonic obstruction with closed-loop obstruction, resulting in colon perforation in a ventilated patient with a cerebrovascular incident. The situation was promptly identified during the first assessment with a surgical consultation and imaging study, resulting in timely surgical intervention which included removing the diseased section of the right colon, creating an end ileostomy, and colostomy. The postoperative contrast study of the remaining colon and colonoscopy confirmed the pseudo-obstruction without finding any blockages in the distal colon and rectum. After the operation, the patient recovered well and was sent home. In conclusion, early clinical suspicion, diagnosis, and prompt management of a complicated ACPO result in a good patient outcome.